Evaluation of Parkin in the Regulation of Myocardial Mitochondria-Associated Membranes and Cardiomyopathy During Endotoxemia - Kim, Matthew; Nikouee, Azadeh; Sun, Yuxiao; Zhang, Qing-Jun; Liu, Zhi-Ping; Zang, Qun Sophia (Frontiers in Cell and Developmental Biology, 2022)
Background: Mitochondrial deficiency is a known pathology in sepsis-induced organ failure. We previously found that mitochondria-associated membranes (MAMs), a subcellular domain supporting mitochondrial status, are impaired in the heart during endotoxemia, suggesting a mechanism of mitochondrial damage occurred in sepsis. Mitophagy pathway via E3 ubiquitin ligase Parkin and PTEN-induced kinase 1 (PINK1) controls mitochondrial quality. Studies described herein examined the impact of Parkin on cardiac MAMs during endotoxemia. Additionally, point mutation W403A in Parkin was previously identified as a constitutively active mutation in vitro. In vivo effects of forced expression of this mutation were evaluated in the endotoxemia model. Methods: Mice of wild type (WT), Parkin-deficiency (Park2-/-), and knock-in expression of Parkin W402A (human Parkin W403A) were given lipopolysaccharide (LPS) challenge. Cardiac function was evaluated by echocardiography. In the harvested heart tissue, MAM fractions were isolated by ultracentrifugation and their amount and function were quantified. Ultrastructure of MAMs and mitochondria was examined by electron microscopy. Mitochondrial respiratory activities were measured by enzyme assays. Myocardial inflammation was estimated by levels of pro-inflammatory cytokine IL-6. Myocardial mitophagy was assessed by co-localization of markers for mitochondria and lysosomes. Parkin activation, signified by phosphorylation on serine 65 of Parkin, was detected by Western blot. Results: Compared with WT, Park2-/- mice showed more severely impaired cardiac MAMs during endotoxemia, characterized by disrupted structure, reduced quantity, and weakened transporting function. Endotoxemia-induced cardiomyopathy was intensified in Park2-/- mice, shown by worsened cardiac contractility and higher production of IL-6. Mitochondria from the Park2-/- hearts were more deteriorated, indicated by losses in both structural integrity and respiration function. Unexpectedly, mice carrying Parkin W402A showed similar levels of cardiomyopathy and mitochondrial damage when compared with their WT counterparts. Further, Parkin W402A mutation neither enhanced mitophagy nor increased Parkin phosphorylation in myocardium under the challenge of endotoxemia. Conclusion: our results suggest that Parkin/PINK1 mitophagy participates in the regulation of cardiac MAMs during endotoxemia. Point mutation W402A (human W403A) in Parkin is unable to alleviated endotoxemia-induced cardiomyopathy in vivo.